Solution
prove
Solution
Solution steps
Manipulating left side
Express with sin, cos
Use the basic trigonometric identity:
Use the basic trigonometric identity:
Simplify
Combine the fractions
Apply rule
Apply the fraction rule:
Apply exponent rule:
Add the numbers:
Rewrite using trig identities
Use the Pythagorean identity:
Simplify
Factor
Factor out common term
Factor
Rewrite as
Apply Difference of Two Squares Formula:
Cancel
Refine
Cancel the common factor:
We showed that the two sides could take the same form
Popular Examples
prove cot(-x)cos(-x)+sin(-x)=-csc(x)prove prove cot(θ)+tan(θ)=csc(θ)sec(θ)prove prove 1/(1-sin^2(x))=1+tan^2(x)prove prove tan(pi/4+a)-tan(pi/4-a)=2tan(2a)prove prove sin^2(x)+3cos^2(x)=3-2sin^2(x)prove
Frequently Asked Questions (FAQ)
Is (cos(θ))/(sec(θ)-tan(θ))=1+sin(θ) ?
The answer to whether (cos(θ))/(sec(θ)-tan(θ))=1+sin(θ) is True